THE INFLUENCE OF FINANCIAL LITERACY AND INCOME ON FAMILY WELFARE IN RATO VILLAGE, BOLO DISTRICT, BIMA REGENCY THROUGH FINANCIAL BEHAVIOR AS A VARIABLE INTERVENING - Afniatun, Nur; Sanurdi; Saadatirrohmi, Siti Ahdina (UIN Mataram, 2023)
This study aims to examine the effect of financial literacy, income on financial well-being, bothdirectly and through financial behavior. The population of this study were all heads of familiesin Rato Village, Bolo District, Bima Regency. The sample of this research is 95 heads of familiesusing the Slovin formula with purposive random sampling technique. This study uses aquantitative approach. Data collection techniques in this study using a questionnaire. The dataanalysis technique uses descriptive analysis and path analysis with the SMARTPLS 4.0 program.The results showed that financial literacy and income had a positive and significant effect onfinancial behavior, financial literacy and income had a positive and significant effect on financialwell-being. Financial behavior had a positive and significant effect on financial well-being. Theresults of the mediating effect show that financial literacy and income have a positive andsignificant effect on financial well-being through financial behavior as intervening variables.